Information literacy of private higher education institution libraries in La Union - Dela Cruz, Estrellita G. (Saint Louis College, City of San Fernando, La Union : [s.n.], 2017)
This descriptive study assessed the information literacy competency of private higher education institution libraries in La Union. Specifically, it sought to look into the level of information literacy competency of respondents in the private higher education institution along the determination of the nature and extent of inforamation needed; the access of the information effectively and efficiently; the evaluation of the information and its source critically; the use of the information to accomplish a specific purpose; and the access and use of inforamation ethically and legally. It also identified the capabilities and inadequacies of the private HEI libraries in providing information literacy competence of their clients.
Bibliography: pages 99-103.
CHED-La Union
Keywords: Libraries